2021
DOI: 10.3389/fphar.2021.762603
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Mechanism of Guchangzhixie Capsule Against Experimental Colitis

Abstract: Ulcerative colitis (UC) is the major type of inflammatory bowel disease (IBD) characterized by an overactive immune response and destruction of colorectal epithelium with intricate pathological factors. Guchangzhixie (GCZX) capsule, included in the Chinese Pharmacopoeia 2020, has been widely utilized against UC. However, the underlying molecular mechanisms have not been elucidated. In the present study, a murine model of experimental colitis was established by orally feeding 4% dextran sodium sulfate (DSS) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…27 Substantial traditional Chinese medicine and other bioactive substances were also verified to be efficacious for intestinal organoids to resist injury induced by pro-inflammatory cytokines TNF-α or INF-γ. 25,[54][55][56] In our present study, great effort was devoted to showcase the enormous potential role of hucMSC-exo in ISCs regeneration vividly, characterized by the increased growth rate, budding rate and average buddings number.…”
Section: Discussionmentioning
confidence: 91%
“…27 Substantial traditional Chinese medicine and other bioactive substances were also verified to be efficacious for intestinal organoids to resist injury induced by pro-inflammatory cytokines TNF-α or INF-γ. 25,[54][55][56] In our present study, great effort was devoted to showcase the enormous potential role of hucMSC-exo in ISCs regeneration vividly, characterized by the increased growth rate, budding rate and average buddings number.…”
Section: Discussionmentioning
confidence: 91%
“…When it comes to the regulation of ROS, we observed that macrophages isolated from the DSS group aggravated the ROS production in intestinal stem cells due to the release of inflammation-promoting cytokines by macrophages ( Yan et al, 2021 ; Yu et al, 2021 ). Since intestinal stem cells are responsible for epithelial replenishment, excessive ROS-induced cell death would exacerbate the compromised epithelial integrity during colitis.…”
Section: Discussionmentioning
confidence: 97%
“…Precessed 660 g DJ, 900 g EC, 660 g ZS, 330 g XR, and 330g FX powder were extracted with water at 95°C for 2 h, and approximately 280 g extraction was obtained. 0.2 g extraction was subjected to LC-30 (Shimadzu)-Hybrid Quadruple time-of-flight mass spectrometer (TOF-MS) with electrospray ionization source (ESI) was utilized to identify the components of CYN as the previous protocol ( Yan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Guchangzhixie capsule is composed of Mume Fructus , Corydalis rhizome , Papaveris pericarpium , Zingiberis rhizoma , Coptidis rhizoma , and Aucklandiae radix , which has been widely utilized against UC. In a murine model of experimental colitis, Guchangzhixie capsule could inhibit experimental colitis progression including alleviating the severity of fecal blood and albumin, shortening colon length, relieving the epithelial structural collapse, and reversing the levels of IL-17 and CXCL1 in mouse serum by hampering macrophage infiltration and suppressing its transition to M1 macrophage polarization ( Yan J. et al, 2021 ). Xian-He-Cao-Chang-Yan formula is composed of Platycodonis Radix , Agrimoniae Herba , Cicadae Periostracum , Acori Tatarinowii Rhizoma , Aucklandiae Radix , and Coptidis Rhizoma , which attenuated the increase of DAI score and the colon shortening, reduced the levels of inflammation in colon tissues and improved DSS-induced acute colitis in mice by suppressing the M1 polarization of macrophages and promoting the M2 polarization of macrophages ( Li J. et al, 2021 ).…”
Section: Tcm Alleviates Uc By Regulating Macrophage Polarizationmentioning
confidence: 99%